2012
DOI: 10.1111/j.1365-2966.2011.20248.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined strong and weak lensing analysis of 28 clusters from the Sloan Giant Arcs Survey★

Abstract: We study the mass distribution of a sample of 28 galaxy clusters using strong and weak lensing observations. The clusters are selected via their strong lensing properties as part of the Sloan Giant Arcs Survey (SGAS) from the Sloan Digital Sky Survey (SDSS). Mass modelling of the strong lensing information from the giant arcs is combined with weak lensing measurements from deep Subaru/Suprime-cam images to primarily obtain robust constraints on the concentration parameter and the shape of the mass distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
407
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(446 citation statements)
references
References 136 publications
35
407
3
1
Order By: Relevance
“…In common with several authors (e.g. Umetsu et al 2010;Oguri et al 2012;Okura & Futamase 2012;Umetsu et al 2015a) we have found that this dependence can be reduced significantly for KSB shape measurement methods if the galaxies upon which the isotropic PSF correction is based are limited to those detected at high signal-to-noise ratio (Okabe et al 2013). We therefore calibrate the isotropic PSF correction, using galaxies detected at very high significance, i.e.…”
Section: Shape Measurement Pipelinementioning
confidence: 99%
See 2 more Smart Citations
“…In common with several authors (e.g. Umetsu et al 2010;Oguri et al 2012;Okura & Futamase 2012;Umetsu et al 2015a) we have found that this dependence can be reduced significantly for KSB shape measurement methods if the galaxies upon which the isotropic PSF correction is based are limited to those detected at high signal-to-noise ratio (Okabe et al 2013). We therefore calibrate the isotropic PSF correction, using galaxies detected at very high significance, i.e.…”
Section: Shape Measurement Pipelinementioning
confidence: 99%
“…The weighting wn (e.g. Hoekstra, Franx & Kuijken 2000;Hamana et al 2003;Okabe et al 2010a;Umetsu et al 2010;Oguri et al 2012) is used to down-weight galaxies whose shapes are less reliably measured, based on the uncertainty in the shape measurement, σg,n, given by…”
Section: Selection Of Background Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the second-order (external shear) and third-order perturbations are included so as to account for asymmetry of the overall lens potential. Interested readers are referred to Oguri (2010Oguri ( , 2015, Oguri et al (2012Oguri et al ( , 2013, and Ishigaki et al (2015) for more detailed descriptions and examples of cluster mass modeling with GLAFIC. Additional details are given in a dedicated paper .…”
Section: Definition Of the Mass Modelmentioning
confidence: 99%
“…We have assembled a list of 130 spectroscopically confirmed strong cluster lenses from the literature, drawing mainly on HST studies of X-ray selected clusters, and strong-lensing clusters from the Sloan Digital Sky Survey (Smith et al 2005(Smith et al , 2009Limousin et al 2007Limousin et al , 2012Richard et al 2010;Christensen et al 2012;Oguri et al 2012;Jauzac et al 2015;Paraficz et al 2016;Umetsu et al 2016). We compare the celestial coordinates of these clusters with the sky localization maps of the BBH merger detections from 2015, finding that none of the known strong-lensing clusters are located The sky localizations of all three GW events intersect the disc of the Milky Way.…”
Section: T H E C L U S T E R L E N S E Smentioning
confidence: 99%